2016
DOI: 10.1039/c5nr06157a
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Au nanostructured surfaces

Abstract: We present here a technological platform for engineering Au nanotopographies by templated electrodeposition on antibacterial surfaces. Three different types of nanostructures were fabricated: nanopillars, nanorings and nanonuggets. The nanopillars are the basic structures and are 50 nm in diameter and 100 nm in height. Particular arrangement of the nanopillars in various geometries formed nanorings and nanonuggets. Flat surfaces, rough substrate surfaces, and various nanostructured surfaces were compared for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 25 publications
2
82
0
Order By: Relevance
“…needle or pillar length) is a factor in cell death [23]; however it is less important than might be expected. Wu et al [24] have experimentally analysed the interactions of bacteria with nanostructured gold surfaces. They proposed that as the height of nanofeatures on the surface decreased, the features became more like "dots", resulting in reduced deformation/stretching of the bacterial cell membrane and thus lower percentage cell death.…”
Section: Introductionmentioning
confidence: 99%
“…needle or pillar length) is a factor in cell death [23]; however it is less important than might be expected. Wu et al [24] have experimentally analysed the interactions of bacteria with nanostructured gold surfaces. They proposed that as the height of nanofeatures on the surface decreased, the features became more like "dots", resulting in reduced deformation/stretching of the bacterial cell membrane and thus lower percentage cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, Wu et al 66 recently reported the antibacterial activity of sparsely ordered nanopillars, nanorings, and nanonuggets, each formed via the electrodeposition of gold onto nanoporous templates, towards methicillin-resistant S. aureus (MRSA) cells. Here, the authors reported >99% cell inactivity aer 2 hours of incubation for all surface structures investigated.…”
Section: Concentrationsmentioning
confidence: 99%
“…The microbicide properties of the nanostructures on the surfaces of black silicon, TiO 2 , polymer, and gold have been demonstrated. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] These surfaces with nanopatterns were generally prepared by a top-down approach on specific materials. Their application will be limited by the material of the substrates and its sophisticated and expensive approach.…”
mentioning
confidence: 99%